Nodulation and yields of soybean (Glycine max L. Merrill) varieties at varying phosphorus fertilizer rates in Lafia, Nigeria - Mangwa, Jibrin Isa; Fauziah Abu Bakar,; Haruna, Ibrahim Muhammad; Jaji, Ibrahim Abdullahi; Mohamad Maulana Magiman,; Sodah, Mohammmad Gwam (Penerbit Universiti Kebangsaan Malaysia, 2024)
Soybean production in Lafia, southern Guinea savanna zone of Nigeria, is impacted by soil phosphorus deficiency, affecting nodulation, nitrogen fixation, and overall crop productivity. Field experiments were conducted in 2018 and 2019 cropping seasons with different phosphorus fertilizer rates (0, 13, 26 & 39 Kg P2 O5 ha-1) and six improved soybean varieties (TGX 1985-10F, TGX 1987-10F, TGX 1448-2E, TGX 1987-62F, TGX 1989-19F & TGX 1835-10E) to determine the effects of phosphorus fertilizer rates on nodulation and yields of soybean varieties. The results showed significant variation in soybean nodulation and yields when different phosphorus fertilizer rates were used. Among the six improved soybean varieties tested, TGX 1989-19F and TGX 1987-62F varieties performed best with 39 kg P2 O5 ha-1. The results also show that plots that received a 39 kg P2 O5 ha-1 produced the highest nodule number (26.3 & 28.7) and nodule weight (203.5 & 221.2 mg/plant) significantly in 2018 and 2019, respectively, compared to those with lower phosphorus rates. The effect of phosphorus fertilizer rates on soybean yields was apparent, with the 39 kg ha-1 phosphorus treatment yielding significantly higher yields than the lower phosphorus treatments. Notably, the TGX 1989-19F variety consistently outperformed the others, yielding the highest yield (1624.0 kg/ ha). Based on the results, it is recommended that soybean farmers in the Lafia region consider increasing their phosphorus rates to 39 kg ha-1 for improved nodulation and subsequent yield gains. The TGX 1989-19F variety, due to its exceptional response to this phosphorus level, could be prioritized for cultivation to maximize returns. However, further research and on-farm trials must validate these findings across multiple growing seasons and farm management practices.